Группы RS-автоматных преобразований - Олийнык, А.С. (Доповіді НАН України, 2010)
Досліджено RS-автомати та групи, ними визначені. Встановлено зв'язки між групами лінійних RS-автоматних перетворень та групами нескінченних унітрикутних матриць. RS-automata and groups defined by them are investigated. Connections between the groups of linear RS-automaton transformations and the groups of infinite unitriangular matrices are established.